Dependences of the noise weight coefficients of digital photo receiver - Anilionienė, Julija; Bajorūnaitė , Rasa (Lietuvos matematikos rinkinys, 1997)
The analytical expressions of the noise weight coefficients of digital photo receiver and calculating results are obtained.